Studies on dune rehabilitation techniques for mined areas at Richards Bay, Natal - Moll, John Bingham (Rhodes University, Faculty of Science, Botany Department, 1993)
Rehabilitation is a dynamic process influenced by factors related to more than one field of ecology. It is therefore necessary to consider all these components when assessing the rehabilitation, although in the initial stages the successful revegetation of the disturbed areas is the most important criterion. Richards Bay Minerals, on whose mining site this project was carried out, is dredge mining heavy minerals on the north coast of Natal, where they have rehabilitated mined areas since 1978. This project has been carried out to establish: 1) The success of their dune forest rehabilitation using quantitative techniques. 2) The available seed bank in their rehabilitation stands. 3) The similarities in the succession taking place in rehabilitation stands compared to the revegetated stands in the vicinity of Richards Bay. 4) The best methods for creating alternative vegetation communities, especially grasslands, with a high species diversity on the mined tailings. This study reviews only the success of rehabilitation of the natural vegetation but other studies focusing on the insect, reptile, mammal and bird populations are also being undertaken by other researchers. No particular method of determining the success of vegetation rehabilitation has been chosen by restoration ecologists. Therefore in this study a broad range of quantitative techniques were used to show whether successional changes are occurring in the vegetation and physical environment. The results obtained from sampling the rehabilitated vegetation have shown that both the species richness and diversity are increasing as the returned vegetation matures. Levels of soil properties such as Sodium, Phosphate, Calcium and percentage organic matter have also risen with increasing stand age. Community complexity is also increasing with stand age, and TWINSPAN and DECORANA plots have separated out the differently aged stands based on their differences. A "pilot" study was done on the seed bank present in the rehabilitation stands. This has shown the presence of large amounts of early successional, mostly herbaceous species. Seeds of later successional and woody species were scarce which may be a result of the sampling intensity used. However seeds of late successional ground cover species were found in the older stands. Comparisons between the natural revegetation of disturbed areas in the vicinity of Richards Bay and the rehabilitation stands revealed similarities in both species composition and complexity. Species richness and diversity values are comparatively similar for the younger revegetated and older rehabilitation stands, and lWlNSPAN and DECORANA analysis techniques clustered the samples recorded from these areas in close proximity on their relative plots. The oldest revegetated sites contain a number of species found in the rehabilitated vegetation but as Acacia karroo has thinned-out in these stands many of these other species are now mature individuals. Attempts at rehabilitating an area of grassland at Richards Bay Minerals has not produced satisfactory species diversity and experimental manipulations were used to try and increase the diversity of the existing Eragrostis curvula dominated community. Of the several treatments used for the manipulation, a combination of burning and further topsoiling was the most successful in reducing Eragrostis importance and in increasing the species richness. Grassland topsoil spread directly onto the bare tailings produced an extensive vegetation covering over a short period but species richness was not significantly greater than for the existing Eragrostis dominated grassland, and further treatments and management needs to continue if this technique is to be employed. Only a limited amount of alien infestation of the rehabilitated areas was evident from the sampling undertaken during this research. As the removal of alien plants is an ongoing process and the rehabilitation stands are continuously monitored to identify any new invaders, this is not expected to become a problem. From the results of work done overseas and the rehabilitation carried out in South Africa it appears that it is possible to return natural vegetation communities on mined areas. That this is a lengthy process is to be expected but by manipulating the vegetation and continuously monitoring the process it may be possible to speed up development. Areas in need of further research have been identified based on the findings of this project. This will help to reinforce the undertaking of management proposals that will enhance the vegetation recovery and the success of the rehabilitation programme.
Keywords: Restoration ecology -- South Africa -- KwaZulu-Natal -- Richards Bay; Sand dune ecology -- South Africa -- KwaZulu-Natal -- Richards Bay; Sand dunes -- South Africa -- KwaZulu-Natal -- Richards Bay; Mineral industries -- Environmental aspects -- South Africa -- KwaZulu-Natal -- Richards Bay